PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO INTERAKTIF PADA MUATAN IPS BERBANTU APLIKASI KINEMASTER KELAS V SDN NO 21/VI RANTAU SULI - Yulia Darniyanti; Wita Nusri; Moh Rosyid Mahmudi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by the difficulty of students understanding special social studies learning material, difficulties in choosing suitable media for the material are still experienced by educators so that it influences student learning outcomes. This study intends to develop interactive learning videos on social studies content assisted by the kineMaster grade V SD application that are valid, practical and effective. The research method used is research (R&D) Research and development. The research model used is the ADDIE Model with stages (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation). The five stages are carried out through needs analysis, curriculum analysis, and character analysis. Based on the results of the research that has been carried out, the validity of the interactive video media was obtained from 3 expert validators, indicating that the interactive video media obtained an average of 85.86% in the very valid category, the results of the interactive video practicality were assessed from the educator's response questionnaire and students to the interactive video, totaling 1 teacher and 14 students in class V at SDN No 21/ VI Rantau Suli, obtained an average of 92.94% categorized as very practical. The effectiveness of interactive videos obtained an average of 84.16% categorized as very effective. Thus it can be concluded that the interactive videos that have been made are very valid, practical, and effective for use in class V SDN No 21/ VI Rantau Suli.